Characteristics of the monad and dyad in Theologumena arithmeticae attributed to Iamblichus Chalcidensis - Woszczyk, Agnieszka (Folia Philosophica, 2012)
The paper presents characteristics of the monad and dyad which might be found in aritmological treatise attributed to Iamblichus Chalcidensis. The treatise deals with the nature of and relation between principles of numbers - the monad and dyad. It contains mathematical analyses linked with traditional Greek theology, and ontological characteristics of the principles are derived even from etymological arguments. The treatise presents many problems, final solutions of which, for historical reasons, needs to remain guesswork. It is probable that Iamblichus, because of his attention for Pythagoreism, addressing the claism of Nicomachus, Antonius and “the ancients”, was in fact presenting also fragment of his own teaching concerning numbers and principles which organise the universe.